Analisis Keamanan Jaringan Wifi di MI Inwanul Huda - Arif Nur Iman; Muchammad Sholeh (Fakultas Teknik, Universitas Muhammadiyah Prof. Dr. Hamka, Jakarta, 2024)
This study aims to analyze the level of Wi-Fi network security at MI Inwanul Huda using quantitative methods, with a technical network testing approach and user surveys. The test results show that the Wi-Fi network at MI Inwanul Huda has several security gaps, including the use of suboptimal WPA2 encryption, weak passwords used, and device firmware that has not been updated. The device configuration evaluation also found that the firewall had not been properly activated, and some devices used default password settings that were vulnerable to exploitation. A survey of 30 network users showed that 70% of users did not understand basic network security measures, while 65% used the same password for various services. This indicates low user awareness of network security. Recommendations proposed include improving technical security through the implementation of WPA3, regular device updates, and user education regarding network security practices. With these steps, it is hoped that the Wi-Fi network at MI Inwanul Huda can support technology-based learning more safely.